Effects of repeated-sprint training in hypoxia on sea-level performance: A meta-analysis - Brocherie, F.; Girard, O.; Faiss, R.; Millet, G. P. (Sports Medicine, 2017)
Background: Repeated-sprint training in hypoxia (RSH) is a recent intervention regarding which numerous studies have reported effects on sea-level physical performance outcomes that are debated. No previous study has performed a meta-analysis of the effects of RSH. Objective: We systematically reviewed the literature and meta-analyzed the effects of RSH versus repeated-sprint training in normoxia (RSN) on key components of sea-level physical performance, i.e., best and mean (all sprint) performance during repeated-sprint exercise and aerobic capacity (i.e., maximal oxygen uptake [VO2max]). Methods: The PubMed/MEDLINE, SportDiscus®, ProQuest, and Web of Science online databases were searched for original articles—published up to July 2016—assessing changes in physical performance following RSH and RSN. The meta-analysis was conducted to determine the standardized mean difference (SMD) between the effects of RSH and RSN on sea-level performance outcomes. Results: After systematic review, nine controlled studies were selected, including a total of 202 individuals (mean age 22.6 ± 6.1 years; 180 males). After data pooling, mean performance during repeated sprints (SMD = 0.46, 95% confidence interval [CI] -0.02 to 0.93; P = 0.05) was further enhanced with RSH when compared with RSN. Although non-significant, additional benefits were also observed for best repeated-sprint performance (SMD = 0.31, 95% CI -0.03 to 0.89; P = 0.30) and VO2max